2020
DOI: 10.34172/apb.2021.084
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory Effect of Rutin on the Antitumor Activity and Genotoxicity of Cisplatin in Tumor-Bearing Mice

Abstract: Purpose: Cisplatin is a cancer chemotherapeutic drug that has been extensively used in the treatment of a variety of cancers. However, the full usage of cisplatin is limited due to its treatment associated development of multiple side effects in the host. In the present study, the modulatory effect of rutin, a type of flavonoid, on the cisplatin mediated antitumor activity and allied genotoxicity in ascites Dalton’s lymphoma (DL)-bearing mice were investigated. Methods: The antitumor activity was determined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…11 In addition, several reports showed that rutin protects against several tumor types, including lung, colorectal, cervical, prostate, breast, bladder, and breast cancer. [27][28][29][30][31][32][33][34] Rutin also causes cell cycle arrest, apoptosis, and inhibits the growth of human colon cancer cells, according to other studies. 27,30,32,[35][36][37] Rutin also affects cisplatin's anticancer efficacy and genotoxicity in tumor-bearing animals.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…11 In addition, several reports showed that rutin protects against several tumor types, including lung, colorectal, cervical, prostate, breast, bladder, and breast cancer. [27][28][29][30][31][32][33][34] Rutin also causes cell cycle arrest, apoptosis, and inhibits the growth of human colon cancer cells, according to other studies. 27,30,32,[35][36][37] Rutin also affects cisplatin's anticancer efficacy and genotoxicity in tumor-bearing animals.…”
Section: Discussionmentioning
confidence: 80%
“…27,30,32,[35][36][37] Rutin also affects cisplatin's anticancer efficacy and genotoxicity in tumor-bearing animals. 33 Furthermore, rutin has been shown to promote autophagy mediated by p53 in human hepatoma Hep-G2 cells, while others have shown that rutin inhibits Sorafenib-induced Chemoresistance and Autophagy in hepatocellular carcinoma through modulating the BANCR/ miRNA-590-5P/OLR1 axis in hepatocellular carcinoma. 25,38 In spite of great efforts done, the detailed pharmacological actions of rutin on tumor cells is still needs to be further clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Both drugs had a similar CA inducing capability and affected the mitotic index of the cells ( Azab et al, 2019 ). An escalation in the incidence of micronuclei in the peripheral blood cells of mice that underwent continuous injection of cisplatin was detected during the assay of micronuclei ( Prasad and Prasad, 2021 ).…”
Section: Reproductive Toxicity and Genotoxicity Of Platinum Drugsmentioning
confidence: 99%